Polyamine Content of Enteral Nutrition Formulas: Effect of Daily Intake on the Feeding Tolerance of Patients During the First Week in the Intensive Care Unit - Manuel Sánchez; Eva Rodríguez-Hernández; Lorena Suárez; Begoña Cantabrana; María González-García (Applied Sciences)
Enteral nutrition (EN) formulas are necessary for critically ill patients to meet their metabolic requirements. Polyamines (putrescine, spermidine, and spermine) are crucial dietary components, with spermidine being particularly interesting due to its multiple proposed benefits. The requirements for and intake of polyamines have yet to be investigated in adult patients hospitalised in intensive care units (ICUs) who are exclusively fed via commercial EN formulas. The aim of this study was to determine the polyamine content and other biogenic amines of EN formulas and the total intake and gastric residual volume (GRV) in adult ICU patients during their first seven days of hospitalisation. The amines were analysed in 16 EN formulas using high-performance liquid chromatography (HPLC). The clinical data of eight patients of both sexes aged 47 to 77 admitted to the ICU were analysed. Differences existed among the analysed EN formulas. The N-acetyl putrescine content was higher than that of the remaining amines. The daily intake of polyamines in the ICU was less than 100 μmol (the dietary intake is above 400 μmol). An inverse correlation existed between total daily polyamine intake and daily GRV, without effects from other biogenic amines being analysed. Polyamine intake in critically ill patients receiving EN is low and could impact these patients’ feeding tolerance. These findings underscore the need for further research to explore the clinical implications of increasing the polyamine content of EN formulas.